Juvenile justice - Baletti, James T. (Nova Science Publishers, 2008)
Juvenile justice : legislative history and current legislative issues / Blas Nuñez-Neto -- Juvenile justice : rights during the adjudicatory process / Alison M. Smith -- Juvenile justice : overview of legislative history and funding trends / Blas Nuñez-Neto) -- Juvenile justice : funding trends / Blas Nuñez-Neto